IR Spectrum and Structure of a Protonated Disilane: Probing the SiHSi Proton Bridge1. Issue 5 (20th December 2012) - Savoca, Marco; Langer, Judith; Dopfer, Otto
<x xml:space="preserve">Abstract</x> Structure elucidation: The IR spectrum of the protonated disilane Si2H7+ has been derived by resonant IR photodissociation spectroscopy of weakly bound Si2H7+⋅Ne clusters (see picture). Analysis of the spectra provides the first characterization of this fundamental polysilane cation and direct evidence for the nonlinear SiHSi proton bridge with a three‐center two‐electron bond.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>